Penggunaan Aplikasi Google Classroom Sebagai Metode Pembelajaran Daring Selama Pandemi Covid-19 - Mirza Ghulamudin; Maufur; Beni Habibi (Universitas Pancasakti Tegal, 2020)
Covid-19 has now attacked Indonesia, where the spread of the disease is very fast. Not only in Indonesia, but all corners of the world are currently experiencing a health crisis. In the beginning, the spread of Covid-19 had an impact on economic activity which began to sluggish. This also has an impact on the education system in Indonesia. Until several countries decided to close schools and universities. In an effort to prevent the spread of covid-19, the World Health Organization (WHO) recommends temporarily stopping activities that would potentially cause crowds. Even during the outbreak, covid-19 in Indonesia, there were many ways that the government did to prevent its spread through social distancing. Kemendikbud instructed through the Ministry of Education and Culture (Kemendikbud) Directorate of Higher Education Circular No. 1 of 2020 concerning the prevention of the spread of covid-19 in the world of Education to organize distance learning and advise students to learn from their homes. Teachers and students are starting to be required to follow the current situation by using technology as a distance learning medium. One of the media that is being favored by teachers as a learning medium is the Google Classroom application. This application is an application that can make it easier for students and teachers to create effective learning. Given that students today are a generation who are very familiar with the use of technology. The use of technology in learning is an alternative method used by teachers during the Covid-19 Pandemic.